Resposta autonômica a uma refeição em indivíduos com gastrite leve ou moderada, com e sem infecção por Helicobater pylori - Moreira, Mauro Diniz (2004)
Improvement of postprandial vasovagal complaints after H. pylori (Hp) treatment in three cases led us to assess autonomic response to feeding in Hp patients. Patients with gastritis but testing negative for Hp were used as controls. Standard noninvasive cardiovascular autonomic tests were applied to Hp patients and controls before and after feeding. As a whole, responses to the maneuvers were strictly inside the expected limits indicating a high reproducibility of the tests. On sympathetic tests, standing postprandial BP was lower than pre-prandial in 5/12 Hp patients and in 0/9 controls, P=0.045. Resting postprandial BP before handgrip was significantly lower than pre-prandial in Hp patients (71 ± 8 mmHg vs. 76 ± 6 mmHg, p=0.0068) but not in controls (76 ± 10 mmHg vs. 77 ± 9 mmHg, p=0.61). Regarding parasympathetic tests, the 4-s unloaded exercise test was revealing: initial heart rate response was higher after feeding than pre-prandial again only in Hp group (1.40 ± 0.20 vs. 1.33 ± 0.17, p=0.0195). Among the measurements influenced by both branches of the autonomic system exhibited, a major particularity was seen in the chronotropic response to handgrip. Postprandial heart rate on effort of Hp patients was not higher than pre-prandial (R-R intervals of 660 ± 99 vs. 648 ± 94 msec, p=0.94) in contrast to controls (R-R intervals of 666 ± 39 msec vs. 685 ± 62 msec, p=0.0195). In support to clinical observations that motivate the study, our findings support an exacerbated vagal response to feeding in Hp patients.